Pengurusan projek pembangunan peringkat daerah: penilaian semula autoriti pegawai daerah - Nadzman, Mustaffa (2020)
Management of development projects at the district level is one of the strategies used by the Government to improve the socio-economic development and to create a balance of development between regions in Malaysia. But until the year 2015 data shows that the goal has not been achieved completely as expected. Top-down approach in development planning which has been widely used now creates a paradox in ensuring every project undertaken produces the outcomes as specified. Project management mechanism which was implemented under the Prime Minister Directive No 1/2010 put it as the District Officer's responsibility to ensure that the specified project outcomes can be achieved. However, this function cannot be properly performed due to the unclear structure and authority of the District Officer as development manager at the local level. Problem faced by the District Officer has attracted the attention of scholars since the 1970s. Previous findings indicated that the District Officer suffers from various problems related to the decline of authority. This study aimed to understand the current position of authority of District Officer and identify appropriate mechanisms to strengthen the functions of District Officer in the management of development projects at the district level. Using structural functionalism approach, this study was conducted in the State of Kedah as case studies. Twelve District Officers and a Director of the State Economic Planning Unit were interviewed to collect the required data. The analysis of relevant data was conducted using thematic analysis approach. This study shows that District Officer encounters problem in terms of concrete structure and analytic structure. To solve the problem of concrete structure, this study suggests upgrading the post of District Officer’s grade and restructuring the mechanism development projects’ management by upgrading JKTD to District Action Council (MTD). To solve the problem of analytic structure, this study suggests the enhancement of charismatic leadership qualities of District Officer. This study also contributes to the state of knowledge in the field of public management in Malaysia by suggesting the re-evaluation of the concept of deconcentration in the district administration to the concept of prefectoral deconcentration.